The Motivating Function of Healthcare Professional in eHealth and mHealth Interventions for Type 2 Diabetes Patients and the Mediating Role of Patient Engagement - Guendalina Graffigna; Serena Barello; Andrea Bonanomi; Julia Menichetti (Journal of Diabetes Research)
eHealth and mHealth interventions for type 2 diabetes are emerging as useful strategies to accomplish the goal of a high functioning integrated care system. However, mHealth and eHealth interventions in order to be successful need the clear endorsement from the healthcare professionals. This cross-sectional study included a sample of 93 Italian-speaking type 2 diabetes patients and demonstrated the role of the perceived ability of healthcare professionals to motivate patients’ initiative in improving the level of their engagement and activation in type 2 diabetes self-management. The level of type 2 diabetes patients’ activation resulted also in being a direct precursor of their attitude to the use of mHealth and eHealth. Furthermore, patient engagement has been demonstrated to be a mediator of the relationship between the perceived ability of healthcare professionals in motivating type 2 diabetes patients and patients’ activation. Finally, type 2 diabetes patients adherence did not result in being a direct consequence of the frequency of mHealth and eHealth use. Patient adherence appeared to be directly influenced by the level of perceived healthcare professionals ability of motivating patients’ autonomy. These results offer important insights into the psychosocial and organizational elements that impact on type 2 diabetes patients’ activation in self-management and on their willingness to use mHealth and eHealth devices.